2021
DOI: 10.29080/jhsp.v5i1.455
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus and Bifidobacterium Bacteria Profile in Healthy People and People with Type 2 Diabetes Mellitus

Abstract: Lactobacillus and Bifidobacterium are two genera of gram-positive bacteria that are widely used as probiotic products to improve the composition of the intestinal microbiota but until now the difference in the number of these bacteria in patients with type 2 diabetes mellitus and healthy people in Asia remains unclear. This study conducted a systematic review to analyze the differences in the number of Lactobacillus and Bifidobacterium bacteria in patients with type 2 diabetes and healthy people in Asia. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Pulse wave conduction time method, also known as photoelectric volume pulseography (PPG for short), is a noninvasive method to detect blood volume changes in arterial vessels by using photoelectric sensors [ 22 ]. It makes use of the transmission or reflection principle of light.…”
Section: Continuous Blood Pressure Measurement Algorithmmentioning
confidence: 99%
“…Pulse wave conduction time method, also known as photoelectric volume pulseography (PPG for short), is a noninvasive method to detect blood volume changes in arterial vessels by using photoelectric sensors [ 22 ]. It makes use of the transmission or reflection principle of light.…”
Section: Continuous Blood Pressure Measurement Algorithmmentioning
confidence: 99%
“…This was also corroborated by animal experiments showing that diabetic mice exhibit a greater abundance of the phylum Firmicutes and a lower abundance of Bacteroidetes than healthy mice [ 21 ]. Similarly, the abundance of Bifidobacterium is negatively correlated with T2DM [ 22 ]. Detailed studies revealed an increase in the abundance of a specific species, B. adolescentis , in patients receiving metformin treatment [ 23 ].…”
Section: The Gut Microbiota Is Associated With T2dm and Its Complicat...mentioning
confidence: 99%